Comparison of the international ovarian tumor analysis simple rules scoring system and risk of malignancy index-4 as predictors of ovarian malignancy - Widia, Made Yudha Ganesa Wikantyas; Budiana, I. Nyoman Gede; Mahendra, I. Nyoman Bayu; Sanjaya, I. Nyoman Hariyasa; Suardika, Anom; Winata, I. Gde Sastra (International Journal of Research in Medical Sciences, 2024)
Background: Ovarian cancer is one of the top three most common cancers in women. Most are detected at an advanced stage, so early detection is essential. A scoring system can easily predict an ovarian malignancy. IOTA Simple Rules and RMI-4 are easy-to-implement scoring systems. This study aimed to evaluate the comparison between the accuracy of the IOTA simple rules scoring system and RMI-4 as a predictor of malignancy in ovarian tumor cases at Prof. Dr. IGNG Ngoerah general hospital. Methods: This study used a diagnostic trial design involving 120 ovarian tumor patients undergoing surgery at Prof. Dr. IGNG Ngoerah general hospital, with 100 patients meeting the inclusion criteria. The collected data were tabulated and analyzed using SPSS for Windows ver. 22. Results were considered significant if p≤0.05. Results: From 100 patient samples who met the inclusion criteria, 60 subjects (60%) were ovarian tumors with benign histopathologic results, and 40 (40%) subjects were tumors with malignant histopathology. The majority of ovarian tumors with malignant histopathology were found in the age group >50 years (52.5%), the menopausal group (57.5%), and multiparity (70%). CA-125 levels above 35 U/ml are found in 90% of the population, with details of 92.5% found in populations with malignant histopathological tumors. The AUC values for RMI-4 and IOTA simple rules are 0.846 and 0.925, with the p value for each scoring system being <0.001. Conclusions: This study found that the IOTA simple rules scoring method has a better diagnostic value than RMI-4 scoring.